Relevansi Kajian Pengembangan Masyarakat dalam Mewujudkan SDGs - Sheiful Yazan; Arwemi Arwemi (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2020)
ABSTRAC Sustainability Development has been a topic of discussion since 1992, then it came to be the development concept of UN member states, through the SDGs at the 70th UN General Assembly, September 2015. Development documents reveal the dominant role of government, as the one and only development actor. This paper discusses the relevance of community development studies in this regard